Dataset of microscopic images and infrared spectra of beach sediment samples from Juara, Salang, and Tulai in Tioman Island, Malaysia - Manap, Mohd Rashidi Abdull ; 0000-0001-6648-4843; Imizan, Muhammad Ibadurrahman bin; Dams, Jannik Werner; Rahman, Norizah Abdul; Waini, Fathin Ayunni Zaiffira; Mukhni, Nur Hayatna; Johari, Wan Lutfi Wan (Data in Brief, 2025)
This dataset presents a comprehensive collection of microscopic images, infrared (IR) spectra of particles obtained from beach sediment in Tioman Island, Malaysia. Sediment samples were collected from multiple sites across three selected beaches to identify material composition and assess the concentration of plastic particles, including both microplastics (<5 mm) and macroplastics (>5 mm), in the region. The IR spectroscopic analysis was carried out in the mid-infrared range (4000–370 cm⁻¹), enabling detailed vibrational characterization of compounds present in the samples. By integrating multiple spectroscopic techniques and vibrational calculations, this dataset provides a valuable resource for environmental monitoring, microplastic pollution studies, and material identification in marine ecosystems.
Keywords: ATR-FTIR; Malaysia; Microplastic; Microscopic images; Spectra